”En grupp där kvinnor äntligen får vara proffs”. En kvalitativ studie om gemenskap och kvinnoseparatism i Växtgäris - Ewerlöf,Jessica (2018)
The aim with this thesis is to broaden the understanding of women’s experiences with separatism in the Swedish Facebook group “Växtgäris”. There are few studies written about the importance of separatism for women, and even less about separatism within social networks. I have therefore interviewed four members from Växtgäris who all claim the need of having a place free from men. Of respect, this study is not going to include any of the groups posted material. This is because of the fact that for those who defines themselves as men are strictly not welcomed in the group. I have used a qualitative interview method and analyzed the informant’s experiences through Pierre Bourdieu theory of capital, habitus and field and Estelle Freedman’s thoughts of separatism as a strategy. All the informants in this study were convinced that the community within the group would have looked different if men were involved. Without men they have a safe place where they can exchange experiences and give each other advice for how to take care of their plants.
Keywords: Växtgäris; community; separatism; social networks; field; habitus; structure